2013
DOI: 10.1097/cnq.0b013e31828404d1
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Gluconate

Abstract: Despite infection-prevention initiatives, hospital-acquired infections (HAIs) are still a common occurrence. Chlorhexidine gluconate (CHG) is an important antibacterial agent. Research indicates that the intervention of bathing with CHG can reduce the number of HAIs. Chlorhexidine gluconate is known to reduce the bioload of several bacteria, including multiple strains of methicillin-resistant Staphylococcus aureus. Research regarding the intervention of bathing with CHG was assessed and found to reduce central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…16 The literature varies in regard to the degree with which CHG reduces SSI, although it is a widely accepted practice and recommended in the American Academy of Orthopaedic Surgery Clinical Practice Guidelines. 10,[17][18][19][20][21] Within dermatology, 1 randomized controlled trial evaluated a five-day decolonization protocol of preoperative 4% CHG aqueous solution combined with intranasal mupirocin and found a 7% reduction in infection rates among S. aureus nasal carriers (p , .05). 2 These procedures were predominantly performed on the head and neck, and the researchers were unable to make any recommendations of the effectiveness of decolonization for lower extremity procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The literature varies in regard to the degree with which CHG reduces SSI, although it is a widely accepted practice and recommended in the American Academy of Orthopaedic Surgery Clinical Practice Guidelines. 10,[17][18][19][20][21] Within dermatology, 1 randomized controlled trial evaluated a five-day decolonization protocol of preoperative 4% CHG aqueous solution combined with intranasal mupirocin and found a 7% reduction in infection rates among S. aureus nasal carriers (p , .05). 2 These procedures were predominantly performed on the head and neck, and the researchers were unable to make any recommendations of the effectiveness of decolonization for lower extremity procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeons typically recommend 1 to 3 showers with 4% CHG leading up to the day of surgery or the use of 2% chlorhexidine-impregnated cloths the night before and morning of surgery. 17,19 Full-body showers for 14 days have shown greater microbial reductions with increasing time, 22 which is the basis for our 14-day preoperative decolonization regimen. Occlusive postoperative dressings aim to ensure that residual skin concentrations of CHG can continue to take antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its broad-spectrum activity, the low irritation associated with chlorhexidine has ensured its enduring use in burn wound care. Though it has been most used as a dental antiseptic, a recent study showed a much lower rate of hospital-acquired infections when patients bathed in chlorhexidine gluconate rather than soap and water 26 . While it is pH dependent, the pH of the wound bed has less effect on its activity than on other antimicrobials, most likely due to its low molecular weight 27 .…”
Section: Classificationmentioning
confidence: 99%
“…La mayoría de los estudios sobre las prácticas de higiene se centran en el personal de salud, no en los pacientes y se limitan a la descripción de los elementos instrumentales del procedimiento. Al respecto indican que los cuidados relacionados con la necesidad de higiene más desarrollados son higiene oral, higiene perianal, lavado de manos, sin embargo, se observa deficiente documentación de resultados e impacto y poco reflejo del cuidado de enfermería individualizado (15,39) Se evidencian piezas de investigación y documentales relacionadas con uso de agentes limpiadores, higiene oral y su impacto y asociación con morbilidad y mortalidad por neumonía asociada al ventilador (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) . También numerosos artículos relacionados con la higiene de las manos y control de infecciones (57)(58)(59)(60)(61)(62)(63)(64) y programas de control de infecciones (65)(66)(67) .…”
Section: Necesidades De Investigaciónunclassified